Mammals in Portugal: A data set of terrestrial, volant, and marine mammal occurrences in Portugal - Grilo, C. (2022)
Open Research: The complete data set is available as Supporting Information and are also available in Figshare at https://doi.org/10.6084/m9.figshare.14938437